Chromosomal damage and telomere length in peripheral blood lymphocytes of cancer patients - Vodenkova, Sona; Kroupa, Michal; Polivkova, Zdenka; Musak, Ludovit; Ambrus, Miloslav; Schneiderova, Michaela; Kozevnikovova, Renata; Vodickova, Ludmila; Rachakonda, Sivaramakrishna; Hemminki, Kari; Kumar, Rajiv; Vodicka, Pavel (Oncology reports, 2020)
Accumulation of non‑specific structural chromosomal aberrations (CAs) and telomere shortening contribute to genome instability, which constitutes as one of the hallmarks of cancer. CAs arise due to direct DNA damage or telomere shortening. CAs in peripheral blood lymphocytes (PBL), which are considered to be markers of exposure, have been previously reported to serve a role in the pathophysiology and progression of cancer through mechanisms that are poorly understood. In addition, the prognostic relevance of telomere length (TL) in patients with cancer remains to be elucidated. In the present study, CAs and TL in PBL isolated from patients with newly diagnosed cancer (151 breast, 96 colorectal, 90 lung) and 335 cancer‑free control individuals were investigated. These results were then correlated with clinicopathological factors and follow‑up data. The accumulation of CAs in PBL was observed with increased susceptibility to breast and lung cancer (P<0.0001), while individuals with longer TL were found to be at a higher risk of breast cancer (P<0.0001). Increased chromatid‑type aberrations were also revealed to be associated with lower overall survival of patients with breast and colorectal cancers using a multivariate model. Compared with control individuals, no association was observed between TL and CAs or age in patients with cancer. In conclusion, the present study demonstrates the association between CAs/TL in PBL and the susceptibility, prognosis and survival of patients with breast, colorectal and lung cancer.
Keywords: peripheral blood lymphocytes; breast cancer; Disease-Free Survival; Male; telomerasa; Neoplasms; patient long‑term survival; lokální recidiva nádoru; Telomere Shortening; nestabilita genomu; následné studie; prognóza; chromozomální aberace; Aged; Case-Control Studies; mužské pohlaví; senioři; lymfocyty; Genomic Instability; Follow-Up Studies; zkracování telomer; Chromosome Aberrations; Neoplasm Recurrence, Local; lung cancer; lidé; Telomerase; ženské pohlaví; studie případů a kontrol; Humans; telomery; Lymphocytes; structural chromosomal aberrations; Prognosis; cancer susceptibility; colorectal cancer; nádory; Female; telomere length; lidé středního věku; přežití bez známek nemoci; Telomere; Middle Aged